Mechanisms of SARS-CoV-2 and Male Infertility: Could Connexin and Pannexin Play a Role? - Omolaoye, Temidayo S.; Jalaleddine, Nour; Cardona Maya, Walter D.; du Plessis, Stefan S. (Frontiers in Physiology, 2022)
The impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on male infertility has lately received significant attention. SARS-CoV-2, the virus that causes coronavirus disease (COVID-19) in humans, has been shown to impose adverse effects on both the structural components and function of the testis, which potentially impact spermatogenesis. These adverse effects are partially explained by fever, systemic inflammation, oxidative stress, and an increased immune response leading to impaired blood-testis barrier. It has been well established that efficient cellular communication via gap junctions or functional channels is required for tissue homeostasis. Connexins and pannexins are two protein families that mediate autocrine and paracrine signaling between the cells and the extracellular environment. These channel-forming proteins have been shown to play a role in coordinating cellular communication in the testis and epididymis. Despite their role in maintaining a proper male reproductive milieu, their function is disrupted under pathological conditions. The involvement of these channels has been well documented in several physiological and pathological conditions and their designated function in infectious diseases. However, their role in COVID-19 and their meaningful contribution to male infertility remains to be elucidated. Therefore, this review highlights the multivariate pathophysiological mechanisms of SARS-CoV-2 involvement in male reproduction. It also aims to shed light on the role of connexin and pannexin channels in disease progression, emphasizing their unexplored role and regulation of SARS-CoV-2 pathophysiology. Finally, we hypothesize the possible involvement of connexins and pannexins in SARS-CoV-2 inducing male infertility to assist future research ideas targeting therapeutic approaches.